High CD45 surface expression determines relapse risk in children with precursor B-cell and T-cell acute lymphoblastic leukemia treated according to the ALL-BFM 2000 protocol - Cario, Gunnar; Rhein, Peter; Mitlöhner, Rita; Zimmermann, Martin; Bandapalli, Obul Reddy; Romey, Renja; Moericke, Anja; Ludwig, Wolf-Dieter; Ratei, Richard; Muckenthaler, Martina; Kulozik, Andreas; Schrappe, Martin; et al. (Haematologica, 2014)
Further improvement of outcome in childhood acute lymphoblastic leukemia could be achieved by identifying additional high-risk patients who may benefit from intensified treatment. We earlier identified PTPRC (CD45) gene expression as a potential new stratification marker and now analyzed the prognostic relevance of CD45 protein expression. CD45 was measured by flow cytometry in 1065 patients treated according to the ALL-BFM-2000 protocol. The 75th percentile was used as cut-off to distinguish a CD45-high from a CD45-low group. As mean CD45 expression was significantly higher in T-cell acute lymphoblastic leukemia than in B-cell-precursor acute lymphoblastic leukemia (P
Gesehen am 09.10.2020